STUDENTS' LEARNING INTEREST WITH THE ZONING SYSTEM IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS IN STATE HIGH SCHOOL 1 RENGAT - Zainudin; Risnawati; Miftahir Rizqa (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The aim of this research is to determine students' interest in learning with a zoning system in Islamic Religious Education subjects at Rengat 1 State High School and the factors that influence students' interest in learning with a zoning system. This research is a type of quantitative descriptive research. Data collection techniques were carried out using interviews, questionnaires and documentation. Data analysis techniques use quantitative descriptive techniques with percentages. The population in this study were 152 students who entered SMAN 1 Rengat via the zoning route. The sample in this study was 38 people. The sampling technique uses random sampling. The results of the research concluded that students' interest in learning with the zoning system in PAI subjects at SMAN 1 Rengat, their interest in learning was in the Very Good category, with a percentage of 81.68%. The factors that influence it consist of internal factors (feelings or emotions, motivation, talent, intelligence) and external factors (environment, infrastructure). These two factors equally influence students' interest in learning. Therefore, to achieve optimal learning interest, the participation of both is needed.